Model Test of the Water and Sand Mixture Inrush in the Mining-Induced Caving Zone. (17th June 2022) - Liang, Yankun; Zhang, Chaoli; Wang, Wenxue; Shen, Xiangyang; Jia, Minghui
Abstract : In western China coal mines, the mining-induced caving zone is regarded as a main pathway for water and sand inrush mixture hazards. The paper experimentally studied the flow behavior and the mechanism of water and sand mixture through mining-induced caving zones. Transport experiments are performed by using a laboratory-scale model, and the caving zone is modelled by using different sizes of glass beads. Four different sand sizes are used for the sand layer. The test results reveal that the mass flow rate of sand and water mixture increases with the increase of the initial water head. And an equation is proposed for the mass flow rate of sand and water mixtures that correctly reproduces the data for all the conditions. In addition, the sudden decreases in water head loss is monitored at the commencement of the water and sand flow, which would result in a large number of sand particles that rapidly start up and make the kinetic energy transfer from water to sand.